Effect of surface pretreatments on resin composite bonding to PEEK - Silthampitag P. (2017)
© 2016. Dental Materials Journal. All Rights Reserved. This study evaluated the effect of surface pretreatments on resin composite bonding to polyetheretherketone (PEEK). Four groups of surface pretreatment (no pretreatment, etched with 98% sulfuric acid, etched with piranha solution and sandblasting with 50 μm alumina) were performed on PEEK. Surface roughness, Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) analysis were examined. Shear bond strength (SBS) and interface characteristics were also evaluated after the specimens were bonded with resin materials. Two-way ANOVA analysis revealed significance on two main effects and interactions. Tukey’s multiple comparisons test showed that the SBS of resin composite on PEEK were the highest in the group etched with 98% sulfuric acid and bonded with Heliobond® (p < 0.05). All pretreatments produced similar spectra of FTIR patterns. SEM demonstrated porosities and pitting from chemical etching, which suggested a significant influence on the adhesion between PEEK and resin materials.